PENGARUH PENGGUNAAN PERMAINAN TRADISIONAL GUNDU TERHADAP PEMAHAMAN KONSEP PENGUKURAN PANJANG - Fajriah, Nurul (JURNAL e-DuMath, 2017)
This study aims to find the effect of using the traditional game of marbles to the understanding of the concept of length measurement. The method used in this study is a quasi-experimental research. The study population was grade II SDN 8 Negeri Katon, Pesawaran. This study uses total sampling so that the two classes were used that II A and II B respectively numbered 31 peopleâs. Data collected by the test results of study and the data were analyzed with quantitative statistics. The results showed that there are significant differences in the understanding of measurement concepts between students who learn to use traditional game of marbles with students who learn by direct learning model. Understanding the concept of measuring the length of the student using the traditional game of marbles showed higher results than students who learn by direct learning model.